Pengaruh Metode Jarimatika terhadap Hasil Belajar Matematika pada Siswa Kelas 3 SDN 13 Parittiga Bangka Barat - Puput, Puput Atmasari; Asyraf Suryadin; Yorenza Meifinda (Universitas Muhammadiyah Bangka Belitung, 2024)
This research was motivated by students' low mathematics learning outcomes, especially in fraction material, as well as other factors, namely that during learning activities, the learning methods used by teachers were less varied, making students less likely to understand fraction material. This research aims to determine how the Jarimatics method affects mathematics learning outcomes for grade 3 students at SDN 13 Parittiga, West Bangka. This research uses quantitative research with a